Large-scale carbon and nitrogen isotopic investigations into caprine diet and management at Tepe Yahya, southeastern Iran - Melina Seabrook; Jesse Wolfhagen; Suzanne E. Pilaar Birch (PLoS ONE, 2025)
Tepe Yahya, a small urban center in southeastern Iran, was embedded in cross-cultural exchange with the many entities of southwestern Asia. Besides an understanding that caprines dominated the animal economy, we have little knowledge of how these animals were managed. The site was discontinuously occupied from the Neolithic to Sassanian periods (6500 BCE to 200 CE). As one of the longest occupied archaeological sites in Iran, Tepe Yahya provides a unique opportunity to examine whether diversity in caprine management accompanied the site’s development and expanded need for provisioning. We examine the diet of 254 sheep and goats between 6500 and 2000 BCE, the Neolithic to Bronze Age, using carbon (δ13C) and nitrogen (δ15N) stable isotopic analysis, and estimate the percentage of C3 plants in animal diets using a custom isotopic mixing model developed in R with “simmr.” While isotopic averages indicate diet was consistent through time, dietary outliers demonstrate the simultaneous presence of multiple management strategies, with certain animals receiving limited access to the full variety of plants available in the landscape. Goats and sheep show statistically significant differences in the percentage of C3 plants in their diets, with goats always eating higher portions of C3 plants than sheep. These differences are likely a result of human interference rather than substantial environmental changes, which are not reflected in the isotopic values. Increasing isotopic variability over time points to a broader array of caprine management strategies, through greater environmental use or more discrete herds, as well as the introduction of nitrogen-fixing plants into select animal diets. The Tepe Yahya caprines continue to reveal the multifaceted nature of managerial strategies and their relation to urban centers.